PENGARUH BRAND HALAL PADA DAGING SAPI TERHADAP KEPUTUSAN PEMBELIAN MASYARAKAT PASAR RAYA MEKONGGA KABUPATEN KOLAKA. - Nurul Fadillah Sakinah; Muhammad Askari Zakariah; Rina Nur Afifah (Jurnal Syariah Hukum Islam, 2020)
Pasar Raya Mekongga Kolaka is a place where there are many buyers and sellers who make buying and selling transactions and the bargaining process, the large number of goods available makes people decide to shop at Pasar Raya Mekongga Kolaka. The formulation of the problem in this study is whether there is an influence of the Halal Brand on Beef on Public Purchasing Decisions at the Mekongga Raya Market, Kolaka Regency? The purpose of this study was to determine whether there is an effect of Halal Brand on Beef on Public Purchasing Decisions at Pasar Raya Mekongga Kolaka Regency. The research method used is a type of quantitative research with a quantitative approach that is subjected to the halal brand in beef. Then the research procedure carried out includes intensive observation (questionnaires, interviews, and documentation) about the Halal Brand on Beef Against Public Purchasing Decisions at Pasar Raya Mekongga Kolaka Regency. The results of this study indicate that the halal brand has an influence on purchasing decisions of the people of Kolaka district, this is evidenced by the results obtained from the SPSS application which functions to test questionnaires that have been filled in by consumers in the form of statements